2018
DOI: 10.1097/igc.0000000000001243
|View full text |Cite
|
Sign up to set email alerts
|

Small Cell Carcinoma of the Ovary: A Rare Tumor With a Poor Prognosis

Abstract: Small cell carcinomas of the ovary are unilateral tumors primarily arising in premenopausal women. Multimodal treatment with cancer-directed surgery and CT results in a modest increase of a generally poor survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 25 publications
0
32
0
1
Order By: Relevance
“…Serum CA125 was slightly elevated in 15 SSCOHT patients with available data 9. A recent study from the National Cancer Data Base (NCDB) between 2004 and 2014 showed a high frequency of elevated CA125 (271/337, 83.9%) 24. CA125 can potentially be applied as a clinical indicator for SCCOHT although we feel like that the serum level in SCCOHT does not elevate as obviously as that in ovarian epithelial carcinomas.…”
Section: An Overview Of Scchotmentioning
confidence: 81%
See 2 more Smart Citations
“…Serum CA125 was slightly elevated in 15 SSCOHT patients with available data 9. A recent study from the National Cancer Data Base (NCDB) between 2004 and 2014 showed a high frequency of elevated CA125 (271/337, 83.9%) 24. CA125 can potentially be applied as a clinical indicator for SCCOHT although we feel like that the serum level in SCCOHT does not elevate as obviously as that in ovarian epithelial carcinomas.…”
Section: An Overview Of Scchotmentioning
confidence: 81%
“…A combined investigation on 293 SCCOHT patients 10 showed that patients at 40 years or older had a worse outcome than younger patients, but there was no significant survival difference between patients with and without germline SMARCA4 mutations. The 5-year overall survival rate in the NCDB cohort was 24.1% for patients with cancer- directed surgery, and only 18% and 12.3% in patients with stage III and IV respectively 24. Intriguingly, Ghazi A, et al 25 reported a SCCOHT patient that developed after two months of ovarian stimulation for in vitro fertilization and died one month after her initial symptoms.…”
Section: Clinical Behavior and Treatment Of Sccohtmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Approximately one half of patients are diagnosed with advanced-stage disease. 3,[7][8][9] Prognosis is poor; one study reported a mean overall survival (OS) declining from 35 months for stage I disease to 3.3 months for stage IV disease, with 75% of all patients experiencing disease relapse. 4 SCCOHT is associated with germline and somatic SMARCA4 mutations, with biallelic inactivation occurring in 25% to 100% of patients in small case series.…”
Section: Sccoht: Pathogenesis and Historical Treatmentmentioning
confidence: 99%
“…Multiagent chemotherapy regimens vary widely, generally including a platinum agent with taxanes, etoposide, vinblastine, cyclophosphamide, doxorubicin, or bleomycin; external beam radiation may be useful in certain circumstances. [4][5][6]8,[16][17][18] Highdose chemotherapy with autologous stem cell rescue may improve OS. In a prospective SCCOHT trial of 10 patients treated with the PAVEP regimen (ie, cisplatin, doxorubicin, etoposide, and cyclophosphamide), followed by consolidative chemotherapy with autoSCT, seven were long-term survivors.…”
Section: Sccoht: Pathogenesis and Historical Treatmentmentioning
confidence: 99%